2019
DOI: 10.1590/2175-8239-jbn-2019-0019
|View full text |Cite
|
Sign up to set email alerts
|

Hyponatremia in elderly patients with fragility fractures of the proximal femur: a cross-sectional study

Abstract: Introduction: Proximal femur fractures affect the mortality and morbidity of elderly individuals. Recent studies have shown an association between fragility fractures and hyponatremia, a common fluid and electrolyte balance disorder. Objectives: This study aimed to investigate the occurrence of hyponatremia in patients with fragility fractures of the proximal femur. Methods: The authors looked into the data from the medical records of patients admitted to the emergency unit of the Real Hospital Português for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In our study, it was determined that there was no statistically significant difference between in-hospital mortality and one-year survival results between hyponatremic and normonatremic patient groups. Studies previously reported in the literature reveal that chronic hyponatremia is an independent factor that increases the incidence of femoral fracture 15,16 . In recent years, more studies have listed hyponatremia among the pathogenic factors of osteoporosis 17,18 .…”
Section: Discussionmentioning
confidence: 87%
“…In our study, it was determined that there was no statistically significant difference between in-hospital mortality and one-year survival results between hyponatremic and normonatremic patient groups. Studies previously reported in the literature reveal that chronic hyponatremia is an independent factor that increases the incidence of femoral fracture 15,16 . In recent years, more studies have listed hyponatremia among the pathogenic factors of osteoporosis 17,18 .…”
Section: Discussionmentioning
confidence: 87%
“…Moreover, many drug groups such as thiazide diuretics, Renin-Angiotensin-Aldosterone system inhibitors, antidepressants, PPIs, and antipsychotics may cause inappropriate ADH syndrome and hyponatremia in this age group [19,20]. Several studies have shown that loop diuretics are linked to osteoporosis and fracture risk [5,16]. Diuretics eliminate sodium and calcium either indirectly via renal excretion or directly via bone resorption from hyponatremia [14,21].…”
Section: Discussionmentioning
confidence: 99%
“…A fragility fracture is a fracture resulting from a fall from standing height or less. These fractures, which most commonly occur in the hip, spine, or wrist, are an indication that the bones of the body have been weakened by underlying conditions [4,5]. The risk factors for hip fragility fractures are advanced age, sex, race, weight loss, lack of exercise, nutritional disorders, metabolic disorders, smoking, and alcohol use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We excluded 94 articles for violation of eligibility criteria; hence, 41 full text articles were reviewed as previously described. After reading the full text article, nine articles (25)(26)(27)(28)(29)(30)(31)(32)(33) were excluded as non-relevant for the research question (Fig. 1).…”
Section: Data Extraction and Analysismentioning
confidence: 99%